Two new species of the genus Loxopamea Hreblay & Plante 1995 (Lepidoptera: Noctuidae) from China - Gyulai, Peter; Saldaitis, Aidas (Zootaxa, 2015)
The genus Loxopamea Hreblay & Plante, 1995 (Noctuidae, Xyleninae: Apameini) was erected by Hreblay & Plante (1995) with type species Loxopamea albitracta Hreblay & Plante, 1995, comprises seven known species with very restricted range in Himalayan–Sino-Pacific subregions. Recently a detailed revision of the tribe Apameini, including the genus Loxopamea was elaborated by Zilli et al. (2009). Taxonomic nomenclature used in this study is constituted according to that revision. In 2014 two further species of the genus were discovered in Sichuan Province of China during a zoological expedition by A. Floriani & A. Saldaitis, which were recognized as new to science. The descriptions of the new species are presented below.